Pengembangan E-LKPD Berbasis Problem Based Learning pada Materi Ikatan Kimia Kelas XI Fase F SMAN 2 Batang Anai - Tafonao, Leni Anggraeni; Zainul, Rahadian (Universitas Negeri Padang, 2025)
The advancement of digital technology in the era towards society 5.0 has an impact on education, one of which is the transformation of printed teaching materials into electronic forms, namely E-LKPD. The purpose of this study aims to determine the validity and practicality of the e-LKPD developed, using the Plomp model of Research and Development (R&D). The stages carried out in this research are preliminary research, prototyping phase, assessment phase. This research is limited to prototyping. Data collection instruments used validation questionnaires and one to one evaluation, practicality questionnaires. Data processing using Aiken's V formula. Based on the validity test results, the average score was 0.93 with a valid category. The results of the practicality test for teachers and students amounted to 94% and 95% with a very practical category.